A new Paramathes Boursin, 1954 (Lepidoptera, Noctuidae) species from China - Saldaitis, Aidas; Gyulai, Peter (Zootaxa, 2016)
The genera Paramathes was erected by Boursin (1954) for four Xestia-like species, however with slight differences from the Xestia Hübner in their clasping apparatuses. Later this generic name was synonymised with Xestia by Lafontaine (1998). Gyulai, Ronkay, & Saldaitis (2011) treated Paramathes as the subgenera of Xestia. The most recent revision of the Paramathes is presented in the volume 8 of the Taxonomic Atlas of the Eurasian and North African Noctuoidea (Varga et al. 2015), in which authors return to the original concept of Boursin (1954), taking into consideration the configuration of the carinal plate of aedeagus and the bar in the basal area of the vesica in the males and the flap-like shape of the two bilateral lobes of the strongly sclerotized antrum in the females. In the recent article, authors follow this idea, accepting that the question is open to doubt on the taxonomic position of Paramathes.